A monograph of British Belemnitidae - Phillips, John 1800-1874 (Cambridge University Press, 2015)
The nephew of William Smith, John Phillips (1800-1874) was also an influential geologist. Professor of Geology at Oxford, and in part founder of the Oxford University Museum, he notably proposed the three main eras: the Palaeozoic, Mesozoic and Cenozoic. Originally published between 1865 and 1870, this monograph was the first to attempt a review of British belemnites, and was influenced in part by the author's youthful studies of the Yorkshire Jurassic. During the mid-nineteenth century there were many developments in the study of this important fossil group, with the discovery of soft parts, and documentation of diverse faunas across Europe. Phillips' work complemented these advances. Though he died before completing the Cretaceous section, the monograph covers many of the most important species (though, as was common at the time, restricted to the genus Belemnites in the broad sense). It remains a starting point for any study of British belemnites.